Improving the Safety of Medicines in the European Union: From Signals to Action. Issue 3 (6th December 2019) - Potts, Joanne; Genov, Georgy; Segec, Andrej; Raine, June; Straus, Sabine; Arlett, Peter
Abstract : Pharmacovigilance and risk minimization must be planned during drug development and forms a critical part of the regulator's decision on whether a medicinal product can be authorized. Pharmacovigilance systems should ensure proactive monitoring of all authorized medicines throughout their lifecycle in clinical use. Signal detection and management are core activities in pharmacovigilance, rapidly delivering new information on the safety of medicines in real‐world use which helps to fill knowledge gaps. The first 6 years of the European Union (EU) signal management system resulted in 453 recommendations issued by the Pharmacovigilance Risk Assessment Committee (PRAC), of which more than half were for drug labeling changes. The EU pharmacovigilance network has demonstrated its ability to detect and evaluate new drug safety signals. This has resulted in new warnings to guide the safe and effective use of medicines in Europe.